SUBURETERAL MUCOSA INJECTION WITH DETRANOMER/HYALURONIC ACID FOR VESICOURETERAL REFLUX TREATMENT: SYSTEMATIC REVIEW - Tambunan, Nicholas; Rodjani, Arry; Wahyudi, Irfan (Indonesian Journal of Urology, 2017)
Objective: The aim of this study is to search the success rate of detranomer-hyaluronic acid (Dx/HA) used as injection through endoscopy approach and grades of vesicoureteral reflux (VUR) that could affect it success rate. Material & methods: We searched the literatures from MEDLINE database and PubMed from year 2001 until 2013. The data was analyzed using Random Effects Model with the method of Mantzel-Haenzel to analyze the success rates of dextranomer/hyaluronic acid and was determined by 95% Confidence of Interval (CI) disclosure. Meta-regression was performed to adjust the success rate compared with the grade of VUR as covariate. We assessed the heterogeneity by calculating the I2 statistic. All analyses were performed with Stata Statistical Software Version 12.0 (StataCorp). Results: We identified 9 literatures in full review. Of 1105 ureters that were injected with dextranomer/hyaluronic acid, 817 (72%; CI: 67-76%) were successfully treated according to author’s definition. The success rates of Dx/HA for pediatric with grade 1 VUR reached 80% (95% CI: 66-89%), whereas in grade 5 VUR only 50% (95% CI: 34-66%; p<0.05). Conclusion: The overall success rate of dextranomer/hyaluronic acid injection treatment was 72% after 3 months, although success rates varied widely among studies. Preoperative grade of VUR was significantly associated with treatment outcome. Increased VUR grade negatively affected success rates.